Metro Manila : in search of a sustainable future - Ohmachi, Tatsuo ;Roman, Emerlinda R. (Diliman Quezon City, Philippines : University of the Philippines Press, 2002)
The JSPS Manila Project is of particular significance to the Philippines and the University of the Philippines for two reasons. First, it tackles very important environmental problems that have confronted Metro Manila for many years now. Indeed the problems of pollution, contamination, traffic congestion, natural disaster and hazards, and garbage have reached proportions serious enough to cause permanent damage to environment. Second, this project brings together a large a number of colleagues from universities of Japan and the Philippines to tackle the problems from different perspectives. This project has generated a lot of discussions and produced a number of papers, some of which are very technical. The challenge lies not just in understanding the findings and recommendations but in ensuring that the results of the studies translate into meaningful, helpful and "doable" policies and measures that will reduce
Includes bibliographical references and index.
Keywords: ENVIRONMENTAL CONSERVATION, METRO MANILA